Using Link and Major System of Memory to Memorise, Remember and Recall Pharmaceutical Sciences Better - Jayaram, Saravanan; Ramajayam, Santhosh Kumar; Rymbai, Emdormi; Sugumar, Deepa (Indian Journal of Pharmaceutical Education and Research, 2020)
Traditional memory techniques like mnemonics, flashcards and outline have been used to memorise and recall information as rote learning is not something that can be completely avoided in education. Recently, two memory techniques that are considered superior to traditional memory techniques-link and major system of memory are being widely used to memorise a large amount of data in a very short time. The link and major system of memory are based on three basic principles: Observation, association and repetition. These techniques can be used to memorise, remember and recall information in pharmaceutical subjects like botanical names and families in pharmacognosy, drug names and classification in medicinal chemistry, dose and adverse effect of drugs in pharmacology, list of additives in pharmaceutics and interpretation of spectrum in pharmaceutical analysis. The link and major system of memory offer several advantages over traditional memory techniques like mnemonics, flashcards and outline. One of the key advantages of link and major system of memory is that these techniques need no training as they are very simple and intuitive to human beings. The other advantages are: they help students to learn, remember and retain new concepts easily; they help students to sharpen their self-learning skills; they also help students to direct their attention to key concepts and process the material deeply and save a lot of time.
Keywords: Link method of memory; Major system of memory; Rote learning; Observation; association; Pharmaceutical sciences